2D nucleation of CdSe on FTO/glass - Khussurova, Gulnur; Puzikova, Darya; Dergacheva, Margarita; Urazov, Kazhmuhan (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
Cadmium selenide is an important photovoltaic material due to its high absorption coefficient and optimal band gap (1.7 eV) for efficient absorption and conversion of solar radiation. The influence of nanostructures on the behavior of CdSe anodes in photovoltaic cells leads to an interest in the study of its electrochemical deposition process and the peculiarities of nucleation and growth of semiconductor precipitation. However, the growth processes in the electrochemical deposition of cadmium selenide remain little investigated....
Keywords: solar radiation; 2D nucleation